2014
DOI: 10.1182/blood.v124.21.2999.2999
|View full text |Cite
|
Sign up to set email alerts
|

Waldenstrom's Macroglobulinemia Associated Bone Disease the UAMS Experience

Abstract: Introduction: Bone disease in patients with paraproteinemias is typically associated to a diagnosis of of multiple myeloma (MM) and the presence of an IgM monoclonal gammopathy with associated lytic bone abnormalities always suggests the possibility of an IgM MM. Because Waldestrom’s Macroglobulinemia (WM) with lytic bone disease has also been reported in the literature we decided to retrospectively investigate the incidence of bone disease in patients carrying a diagnosis of WM and to evaluate the clinical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Guidelines for the use of diagnostic imaging modalities to identify bone involvement in WM/LPL are lacking. In a retrospective study of highly selected patients, PET-CT and MRI demonstrated bone disease in 24% and 17% of the cases, respectively [ 10 ]. In our patient, the areas of bone involvement were not FDG-avid.…”
Section: Discussionmentioning
confidence: 99%
“…Guidelines for the use of diagnostic imaging modalities to identify bone involvement in WM/LPL are lacking. In a retrospective study of highly selected patients, PET-CT and MRI demonstrated bone disease in 24% and 17% of the cases, respectively [ 10 ]. In our patient, the areas of bone involvement were not FDG-avid.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 Rothschild et al 8 documented in their clinical case study that WM/LPL has a combination of features of other hematologic malignancies such as myeloma and leukemia on both macroscopic and radiologic examination of osteolytic lesions. Papanikolaou et al 9 substantiated this rather unusual presentation in WM/LPL on imaging studies such as PET‐CT (positron emission tomography‐computed tomography) or MRI (magnetic resonance imaging), while some other studies even reported improvement of lytic lesions with treatment 10,11,12,28,29 …”
Section: Introductionmentioning
confidence: 96%
“…However, the biology of these differences in bone lesions between MM and WM/LPL are poorly understood. In a study by Papanikolaou et al, focal lytic bone disease was evident in 17 to 24% of WM cases when investigated retrospectively using either MRI (magnetic resonance imaging) or PET-CT (positron emission tomography-computed tomography) imaging, respectively [11]. Consequently, multiple studies have substantiated this rather unusual presentation in WM/LPL, while some even reported improvement of lytic lesions with treatment [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%